The Evaluation Of rs11776042 Polymorphism Effect On Colorectal Cancer Risk In The Iranian Population: A Case-Control Study - Marzieh Mobaraki; Seyed Abdolhamid Angaji; Ehsan Nazemalhosseini-Mojarad; Sedigheh Arbabian; Hamid Asadzadeh Aghdaei (Basic & Clinical Cancer Research, 2022)
Background: Recently, it has been shown that, piRNAs as a new class of non-coding RNAs (ncRNAs), play crucial roles in germline development and carcinogenesis. Despite this, the study on the effects of piRNAs polymorphism (piR-SNP) on colorectal cancer (CRC) risk is scarce. We evaluate the impact of rs11776042 in piRNA 015551 on CRC initiation and development in the Iranian population.